Expression analysis of PINK1 and PINK1-AS in multiple sclerosis patients versus healthy subjects - Patoughi, Mona; Ghafouri-Fard, Soudeh; Arsang-Jang, Shahram; Taheri, Mohammad (Nucleosides, nucleotides & nucleic acids, 2021)
Recent investigations which have aimed at unraveling the etiology of multiple sclerosis (MS), have underscored the role of mitochondria in this disorder. PINK1 gene codes a serine/threonine kinase that protects mitochondria and maintains its normal function. In the current project, we quantified expression levels of PINK1 and a long non-coding RNA which is transcribed antisense to this gene (PINK1-AS) in the peripheral blood of MS patients versus normal persons. Peripheral expression of PINK1-AS was remarkably higher in MS patients compared with healthy individuals. A significant difference in PINK1-AS level was also recognized in male patients compared with male controls. But, the difference was not remarkable between female subgroups. Expression of PINK1 was not different between MS patients and healthy persons. Univariate analysis showed significant differences in age, disease duration, progression index and age at disease onset between males and females (P values of 0.041, 0.001, <0.0001 and 0.007 respectively). There was a trend toward correlation between expression levels of PINK1 and PINK1-AS (r = 0.26, P = 0.074). However, expressions of either genes were correlated with any of the demographic or clinical features. Based on the altered expression of PINK1-AS in the peripheral blood of MS patients, PINK1-AS might be a putative culpript in the pathogenesis of MS. We recommend conduction of additional studies to unravel the mechanism of PINK1-AS partake in the MS.